GAMBARAN STATUS GIZI BERDASARKAN INDEKS MASA TUBUH DAN LINGKAR LENGAN ATAS - Pradika, Jaka; Sumarna, Felisianus; Amelia, Lince; Astuti Purnamawati, Ditha; Patama, Kharisma; Amrullah, Syahid (Literasi Intelektual, 2024)
Background: Nutritional status is one of the important elements in shaping health status. The utilization of nutrients in the body is influenced by two factors, namely primary and secondary. Primary factors are conditions that affect nutritional intake due to the improper arrangement of food consumed, while secondary factors are nutrients that do not meet the body's needs due to disturbances in the utilization of nutrients in the body. Objective: The purpose of this study was to determine the Nutritional Status of Body Mass Index (BMI) and Upper Arm Circumference (LILA) at SMP Negeri 04 Retok Acin Kuala Mandor B. Methods: This research method is descriptive with a cross sectional approach. Results: The results showed that based on the BMI value, the most respondents were found in the normal category, namely 31 people (57.4%), and the second category was thin there were 18 people (33.3%), and the fat category was 5 people (9.3%) while obesity did not exist in total from this category there were 54 people with a percentage (100.0). Based on LILA, the results obtained with the percentage of categories at risk of Chronic Energy Deficiency (CHD) were more, namely 46 people (85.2%), and not at risk of CHD as many as 8 people (14.8%). Conclusion: Based on BMI values, most of the students of SMPN 4 kuala mandor B have normal BMI categories as many as 31 people (57.4%). and based on LILA values, most students are at risk of SEZ, namely 46 people (85.2%).